1998
DOI: 10.1099/0022-1317-79-3-587
|View full text |Cite
|
Sign up to set email alerts
|

Proline-138 is essential for the assembly of hepatitis B virus core protein.

Abstract: In small RNA viruses, arm-like segments located at the N or C termini have been suggested as mediators in the assembly of the capsid proteins. In many cases the arms of several subunits converge at a common point (the symmetry axis). Recent advances in studies of the hepatitis B virus (HBV) core protein attest the convergence of the segments preceding the protamine region, around the symmetry axis, where five or six HBc protein subunits converge. We report a mutation study of the region that we have suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This rare sequence conservation indicates highly crucial residues. The cruciality has already been shown for the three C-terminal residues (gly111 to pro138), which are essential for folding or capsid formation [ 54 , 59 , 60 ]. The functions of his47 have not been studied systematically.…”
Section: Discussionmentioning
confidence: 99%
“…This rare sequence conservation indicates highly crucial residues. The cruciality has already been shown for the three C-terminal residues (gly111 to pro138), which are essential for folding or capsid formation [ 54 , 59 , 60 ]. The functions of his47 have not been studied systematically.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that Cp138 is not assembly competent (Birnbaum and Nassal, 1990; Beames and Lanford, 1993; Metzger and Bringas, 1998), and we have found that Cp139 shares this property. Moreover, a monoclonal antibody that bound to Cp140 failed to react with Cp138 (Salfeld et al ., 1989), suggesting a different conformation.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal portion (aa 1–150) of core protein is capable of self- assembling into nucleocapsids even in the absence of the C terminus (Birnbaum & Nassal, 1990 ; Nassal, 1992 ; Halton et al , 1992 ). In contrast, core mutants bearing a small insertion, substitution or deletion in the N-terminal domain of HBV core protein (Beames & Lanford, 1995 ; Metzger & Bringas, 1998 ; Konig et al , 1998 ) or woodchuck hepatitis virus (WHV) core protein (Yu et al , 1996 ) fail to form nucleocapsids. However, studies on duck HBV show that the core protein N-terminal additions have various effects on capsid formation depending on the nature of the extension peptides (von Weizsacker et al , 1996 ; Kock et al , 1998 ).…”
Section: Introductionmentioning
confidence: 99%